2018
DOI: 10.1080/02626667.2018.1552788
|View full text |Cite
|
Sign up to set email alerts
|

Monthly streamflow forecasting using neuro-wavelet techniques and input analysis

Abstract: Combinations of low-frequency components (also known as approximations) resulting from the wavelet decomposition are tested as inputs to an artificial neural network (ANN) in a hybrid approach, and compared to classical ANN models for flow forecasting for 1, 3, 6 and 12 months ahead. In addition, the inputs are rewritten in terms of the flow, revealing what type of information was being provided to the network, in order to understand the effect of the approximations on the forecasting performance. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Aziz et al ( 2014) adopted a regional flood frequency analysis with the use of artificial neural networks to estimate flood quantiles in Australia, and it has been found that such an analysis with ANN generates more accurate analysis result. Honorato et al (2019) also applied neuro-wavelet techniques to predict monthly streamflow. These integrated techniques are tested and later found with the accuracy improvement of the models.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Aziz et al ( 2014) adopted a regional flood frequency analysis with the use of artificial neural networks to estimate flood quantiles in Australia, and it has been found that such an analysis with ANN generates more accurate analysis result. Honorato et al (2019) also applied neuro-wavelet techniques to predict monthly streamflow. These integrated techniques are tested and later found with the accuracy improvement of the models.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Each of these connections receives a weight, which determines its impact on the cells it connects. Each cell thus has an input, which allows it to receive information from other cells, but also from what is called an activation function, which in the simplest cases is a simple identity of the result obtained by the input and finally an output (Santos & Silva, 2014;Freire et al, 2019;Santos et al, 2019;Honorato et al, 2019).…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…The aforementioned predictions are also related to crucial aspects of energetic planning, such as pricing strategies, expansion of the installed capacity, and the expected availability of energy for short and medium-term horizons (Honorato, et al, 2018;Siqueira et al, 2018;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%